2018
DOI: 10.4103/1673-5374.230301
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-7 nicotinic acetylcholine receptor agonist treatment in a rat model of Huntington's disease and involvement of heme oxygenase-1

Abstract: Neuroinflammation is a common element involved in the pathophysiology of neurodegenerative diseases. We recently reported that repeated alpha-7 nicotinic acetylcholine receptor (α7nAChR) activations by a potent agonist such as PHA 543613 in quinolinic acid-injured rats exhibited protective effects on neurons. To further investigate the underlying mechanism, we established rat models of early-stage Huntington's disease by injection of quinolinic acid into the right striatum and then intraperitoneally injected 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Clinically, the lead compounds Nefiracetam and PHA 543613, both of which are orally administered, have invaluable mechanisms of action to treat these deficiencies. Nefiracetam is a cholinergic, GABAergic, and glutamatergic agonist developed to enhance cognitive functioning (Malykh & Sadaie, 2010; Moriguchi, 2011), and PHA 543613 is an α7‐nAChR agonist with proven neuroprotective effects in a neurodevelopmental disease model (Foucault‐Fruchard et al , 2018). Cholinergic modulatory effects within the nervous system are many because nAChRs are widely dispersed across the neuronal and synaptic architecture, and acetylcholine additionally affects the release of other neurotransmitters (Picciotto et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the lead compounds Nefiracetam and PHA 543613, both of which are orally administered, have invaluable mechanisms of action to treat these deficiencies. Nefiracetam is a cholinergic, GABAergic, and glutamatergic agonist developed to enhance cognitive functioning (Malykh & Sadaie, 2010; Moriguchi, 2011), and PHA 543613 is an α7‐nAChR agonist with proven neuroprotective effects in a neurodevelopmental disease model (Foucault‐Fruchard et al , 2018). Cholinergic modulatory effects within the nervous system are many because nAChRs are widely dispersed across the neuronal and synaptic architecture, and acetylcholine additionally affects the release of other neurotransmitters (Picciotto et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Alpha7 nicotinic acetylcholine receptor (α7nAChR), firstly identified in the autonomous nervous system, is a ligand-gated ion channel exerted as a regulator in cognitive processes through the modulation of specific neurotransmitters (Marrero et al, 2011; Liu and Su, 2012; Lu et al, 2014). More recently, resident macrophages in different tissues proved to highly express α7nAChR, and the activation of this receptor inhibits the production of inflammatory cytokines, thereby attenuating the local inflammatory response (Yu et al, 2013; Foucault-Fruchard et al, 2018; Meroni et al, 2018). Previous studies demonstrated that the α7nAChR activation mediated bowel, neural, and cardiovascular protection (Yu et al, 2013; Foucault-Fruchard et al, 2018; Meroni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, resident macrophages in different tissues proved to highly express α7nAChR, and the activation of this receptor inhibits the production of inflammatory cytokines, thereby attenuating the local inflammatory response (Yu et al, 2013; Foucault-Fruchard et al, 2018; Meroni et al, 2018). Previous studies demonstrated that the α7nAChR activation mediated bowel, neural, and cardiovascular protection (Yu et al, 2013; Foucault-Fruchard et al, 2018; Meroni et al, 2018). Consistent with these data, the administration of α7nAChR agonist has been shown to effectively prevent acute lung injury via inflammation suppression (Ge et al, 2017; Pinheiro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Much has already been written about potential therapeutic applications of nicotinic signalling for brain disease. Preclinical studies have shown beneficial effects of α7-nAChR agonists in neurodegenerative diseases such as Parkinson’s disease (Stuckenholz et al ., 2013) (Liu et al ., 2012a), Huntington’s disease (Foucault-Fruchard et al ., 2018) and in Alzheimer’s disease (Medeiros et al ., 2014) (Vicens et al ., 2017). However the demonstration, here, of the impact of basal cholinergic tone on the homeostatic phenotype of microglia helps to clarify the nature of anti-inflammatory effects of nicotinic agonists but also shows that the loss of cholinergic tone, in aging and early dementia, likely reduces the brain’s resilience to secondary inflammatory challenges such as infection, surgery or injury.…”
Section: Discussionmentioning
confidence: 99%